In a football bubble and beyond: Cultural transition pathways of Swedish professional football players - Söderlund, E. S.; Stambulova, N. B. (Scandinavian Journal of Sport and Exercise Psychology, 2021)
The objectives of this study were: (1) to explore cultural transition pathways of Swedish professional football players relocated to another European country, (2) to identify shared themes in their transition narratives. We interviewed three professional players who in their early twenties relocated to Italy, Turkey, and Switzerland, and then analyzed their stories using holistic and categorical analyses following the narrative oriented inquiry (NOI) model (Hiles & C?erma´k, 2008). The holistic analysis resulted in creating three core narratives (i.e., re-telling of the participants` stories) entitled: Preparing for the worst-case scenario and saved by dedication to football; Showing interest for the host culture and carrying responsibility as a foreign player; and A step for personal development: from homesickness to being hungry for more. The categorical analysis resulted in 12 shared themes from the players` stories arranged around three phases of the cultural transition model (Ryba et al., 2016). In the pre-transition all the participants were established players searching for new professional opportunities. In the acute cultural adaptation phase, they all prioritized adjustment in football (e.g., fitting in the team, performing). In the socio-cultural adaptation phase, they broaden their perspectives and realized that finding a meaningful life outside of football was just as important to function and feel satisfied as football success.